Implementation Strategy of the Agriculture and Food Security Service to Enhance Food Security in Lebak District - Fauzan, Muhammad Hafizh; Widyastuti, Yeni; Rahmawati (International Journal of Social Sciences Review, 2024)
This research focuses on about how the process of strategy implementation of the Agriculture and Food Security Service in Increasing Food Security in Lebak District. Has the strategy implementation process gone well according to the mechanism or has appropriate based on the rule that has been established. The problem in this research for all this time is the lack of optimal implementation of the strategy based on the rule that has been determined by Lebak district food security service strategic plan 2019-2025, and the rule of Law Number 18-year 2012 food concerning. This research is to gain information on how to implement the strategy of the food security service in improving food security in Lebak district. This research is descriptive qualitative research. This primer data collection technique comes with observation, interview, and documentation, while the secondary data collection technique and the source of other secondary data source of data. The researcher uses the theory strategic management in the dimension of strategy implementation model of Wheelen and Hunger with the indicator of program; budget; procedure. In choosing the informant, the researcher uses purposive techniques. The result of the research shows that implementing the strategy of the food security service in improving food security in Lebak district is still not running well yet. Due to lots of problem that exist in the stage of the reduction of agricultural land in Lebak district due to disaster-prone, lack of sub-district participation in the food self-sufficient village program so that the program has not run optimally, and the finally is lack of experts in counseling from the Lebak district food security strategy.